From the Frontline to the Homefront: The Experience of Israeli Veterans - Solomon, Zahava (Frontiers in Psychiatry, 2020)
In 1948, the state of Israel was created as a homeland for the Jewish people after 2,000 years of persecution and deportations in the diaspora. During the past 72 years, its inhabitants have experienced several wars and numerous terrorist attacks. Therefore, the issue of trauma goes beyond academic study, it is part of daily life. These circumstances have, unfortunately, turned Israel into a natural stress laboratory, which has enabled the systematic research of the biopsychosocial effects of traumatic stress on soldiers and civilians. This article reviews the findings of a series of studies that examine (a) the short- and long-term mental health effects of war on combat veterans; (b) the effects of repeated exposure to war on veterans; (c) trajectories of PTSD; and, specifically, (d) reactivation and (e) delayed-onset PTSD. We present the findings of two decades of systematic trauma research, which have followed the ongoing psychopathological effect of war on veterans. In understanding the ripple effects of trauma, it can be seen that veterans do not leave the events of the war behind once they are home; rather, it is with them wherever they go. Consequently, the trauma has a ripple effect that may carry over to veterans' spouses and offspring. The multiple manifestations and trajectories of both acute and chronic trauma will be presented. Clinical ramifications and implications will also be discussed.